2008
DOI: 10.1103/physrevd.78.063001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of interacting phantom scalar field dark energy in loop quantum cosmology

Abstract: We study the dynamics of a phantom scalar field dark energy interacting with dark matter in loop quantum cosmology (LQC). Two kinds of coupling of the form αρ mφ (case I) and 3βH(ρ φ + ρ m ) (case II) between the phantom energy and dark matter are examined with the potential for the phantom field taken to be exponential. For both kinds of interactions, we find that the future singularity appearing in the standard FRW cosmology can be avoided by loop quantum gravity effects. In case II, if the phantom field is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 84 publications
0
49
0
Order By: Relevance
“…The modified Friedmann equation for LQC is given by (Wu and Zhang 2008;Chen et al 2008;Fu et al 2008)…”
Section: The Modelmentioning
confidence: 99%
“…The modified Friedmann equation for LQC is given by (Wu and Zhang 2008;Chen et al 2008;Fu et al 2008)…”
Section: The Modelmentioning
confidence: 99%
“…The cosmological evolution in LQC has been widely studied for quintessence and phantom DE models [40]. The modified Friedmann equation for Loop Quantum Cosmology is given by [29,41,42]…”
Section: Basic Equations Of Loop Quantum Gravity Modelmentioning
confidence: 99%
“…Jamil et al [42] have investigated the cosmic coincidence problem by assuming the MCG coupled to DM. It has also been found that the future singularity appearing in the standard FRW cosmology can be avoided by loop quantum effects [43]. Chakraborty et al [44] have tested MCG in LQC.…”
Section: Sthc For Vmvcg In Loop Quantum Cosmologymentioning
confidence: 99%